Eslicarbazepine acetate as adjunctive therapy in patients with uncontrolled partial‐onset seizures: Results of a phase III, double‐blind, randomized, placebo‐controlled trial. (22nd December 2014) - Sperling, Michael R.; Abou‐Khalil, Bassel; Harvey, Jay; Rogin, Joanne B.; Biraben, Arnaud; Galimberti, Carlo A.; Kowacs, Pedro A.; Hong, Seung Bong; Cheng, Hailong; Blum, David; Nunes, Teresa; Soares‐da‐Silva, Patrício; et al.
Summary Objective To evaluate the efficacy and safety of adjunctive eslicarbazepine acetate (ESL) in patients with refractory partial‐onset seizures. Methods This randomized, placebo‐controlled, double‐blind, parallel‐group, phase III study was conducted at 173 centers in 19 countries, including the United States and Canada. Eligible patients were aged ≥16 years and had uncontrolled partial‐onset seizures despite treatment with 1–2 antiepileptic drugs (AEDs). After an 8‐week baseline period, patients were randomized to once‐daily placebo (n = 226), ESL 800 mg (n = 216), or ESL 1, 200 mg (n = 211). Following a 2‐week titration period, patients received ESL 800 or 1, 200 mg once‐daily for 12 weeks. Seizure data were captured and documented using event‐entry or daily entry diaries. Results Standardized seizure frequency (SSF) during the maintenance period (primary end point) was reduced with ESL 1, 200 mg (p = 0.004), and there was a trend toward improvement with ESL 800 mg (p = 0.06), compared with placebo. When data for titration and maintenance periods were combined, ESL 800 mg (p = 0.001) and 1, 200 mg (p < 0.001) both reduced SSF. There were no statistically significant interactions between treatment response and geographical region (p = 0.38) or diary version (p = 0.76). Responder rate (≥50% reduction in SSF) was significantly higher with ESL 1, 200 mg (42.6%, p < 0.001) but not ESL 800 mg (30.5%, p = 0.07) than placebo (23.1%). Incidence of treatment‐emergent adverse events (TEAEs) and TEAEs leading to discontinuation increased with ESL dose. The most common TEAEs were dizziness, somnolence, nausea, headache, and diplopia. Significance Adjunctive ESL 1, 200 mg once‐daily was more efficacious than placebo in adult patients with refractory partial‐onset seizures. The once‐daily 800 mg dose showed a marginal effect on SSF, but did not reach statistical significance. Both doses were well tolerated. Efficacy assessment was not affected by diary format used.